Soil-Site Suitability for Finger Millet Crop in Kumarband Sub-watershed Area of Dang District, Gujarat - Shirgire, S. T.; Das, Amaresh; Kumar, Rajkishore (International Journal of Bio-resource and Stress Management, 2018)
The seventeen representative pedons were evaluated for their suitability to finger millet in the soils of different elevation having gently slope (flat plains) to higher degree of sloppy land i.e. at lower 350 m msl (P1 to P5) (higher degree of slope) of Kumarband sub watershed area in the Dang district of Gujarat. The soils of study area were neutral to slightly alkaline in reaction and low to medium in organic carbon. The study suggests that soils at lower elevation finger millet crops were moderately suitable (S2), while in soils of middle elevation finger milletare marginally suitable (S3) except pedon 9 (P9) i.e. not suitable finger millet cultivation . In case of upper elevation, finger millet was marginally suitable (S3) but soils of surrounding area of pedon 4 (P4) are not suitable finger millet cultivation because of higher degree of slope, soil texture, soil depth, stoniness, erosion and soil drainage are the major limitations. Results showed that the suitability classes can be improved if the correctablemajor limitations of soil erosion of hilly sloppy area were the only option to control the limitations which make them moderately sustainable to suitable class through soil amelioration measures.